Disasters’ impact on supply chains and countermeasure strategies: an overview of the academic literature’ nature - Brenda de Farias Oliveira Cardoso; Tharcisio Cotta Fontainha; Adriana Leiras (Brazilian Journal of Operations & Production Management, 2022)
Goal: This paper investigates the nature of the academic literature on the disasters’ impacts on Supply Chains (SC) and the strategies adopted to minimize their adverse effects.